Pengaruh Temperatur Solution Treatment dan Aging terhadap Struktur Mikro dan Kekerasan Copperized-AISI 1006 - Sutarsis, Sutarsis; Vicky, Widia Anggia; Purwaningsih, Hariyati (Jurnal Matematika dan Sains, 2017)
As one of the alloying elements used in low carbon steel, copper can increase the strength of steel without lowering its ductility significantly. Copper increases the strength of steel by precipitation hardening. In this research, copper and AISI 1006 steel were alloyed by immersing the pre-heated steel into molten copper. After the imersion process, the precipitation hardening was performed with variations in temperature of solution treatment and aging. From the results of this study, it was found that the solution treatment temperature did not affect the phase of copperized-AISI 1006, but the aging process affected the formation of secondary phase. The increase of solution treatment temperature is proportional to the increase of copperized-AISI 1006 average grain diameter. In contrast, the use of aging temperature of 450oC obtained the smallest average grain diameter than others, in the amount of 49,23 μm and 50,26 μm for sample that previously being  solution treatment at 800 and 900oC. Besides, the increase of the solution treatment temperature is inversely  proportional to the hardness number of copperized-AISI 1006. However, the aging temperature of 450oC obtained the highest hardness number than other aging temperature, in the amount of 119,47 VHN and 115,75 VHN for sample that previously being solution treatment at 800 and 900oC.